KEEFEKTIFAN MEDIA PEMBELAJARAN LOOSE PARTS TERHADAP KARAKTER CINTA LINGKUNGAN DAN KREATIVITAS ANAK USIA DINI - Christin Dwi Putri Septian; Dini Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Children who possess abilities and intelligence above average, or who can be described as having high creative abilities, are known as exceptionally intelligent children with special talents. This aptitude and intelligence can be demonstrated in a number of contexts, including academia, the arts, sports, music, and more. Every child has unique intelligence and skill sets at birth. Three categories of children's intelligence exist: below average, medium (normal), and above average. It goes without saying that their disparities in aptitude and intelligence make them exceptional. So what precisely qualifies as a child who is exceptionally bright and talented? Why do gifted and exceptionally intelligent kids get classified as special needs kids? Which learning models and traits distinguish children who are exceptionally intelligent and talented? Let's examine the following justification.